„Van másféle híre, de miért nem hangosabb?”: A debreceniség mintázatairól – Meliustól Téreyig - Szirák, Péter (Studia Litteraria, 2021)
In the first decades of the 21st century Debrecen is once again preoccupied with the question of its existence, as in this time period a number of major conferences were devoted to the overview of the city’s cultural media and media representations (arts, mass culture, tourism), moreover, with the survey of its local identity, local economy, contemporary arts and popular culture. The conference, titled A debreceniség mintázatai: Városi identitás és a lokális emlékezet rétegei a kora újkortól napjainkig (Patterns of Debrecenness: Layers of Urban Identity and Local Memory from Early Modern Era to the Present), organised by the Hungarian Memory Places Research Team of the Institute of Hungarian Literature and Culture at the University of Debrecen in January 2018 was also part of this series of conferences. The conference, starting out from the discourse of memory place archaeology but also including the present, questioned the diverse Debrecen-representations’ potential to form identity. The 9th volume of the esteemed series, Loci Memoriae Hungaricae, collected the materials of this colourful and efficient discussion. This complex interdisciplinary and inter-artistic volume is separated into five major segments: starting with the stereotypes, the systematic discussion of the concept of „debreczeniség”/debreceniség (Debrecenness) and the effect of the culture creating force of reformed Protestantism, through the interpretations of literary representations, urban texts, and social history-historiographic interconnections, finishing with the descriptions of the architecture of recent past and present, and urban marketing. The present review, now extended into a study, responds to the papers included in the volume by maintaining an animated discussion with them.